Assessment of knowledge and practice of private practitioners regarding tuberculosis control in Ethiopia - Solomon A Yimer; Carol Holm-Hansen; Gunnar Bjune (Journal of Infection in Developing Countries)
Introduction:  Ethiopia has a growing private health sector. In recent years, the directly observed treatment short course (DOTS) strategy was initiated in selected private health facilities in the country. The objective of the present study was to assess knowledge and practice of private practitioners in tuberculosis (TB) control in Amhara Region, Ethiopia. Methodology: An institution-based cross-sectional study was conducted among 112 private practitioners selected from all private health facilities in the region. The study was conducted between May and August 2008 and data was collected using a semi-structured questionnaire. Group differences were analyzed using the chi-square test. Results: Fifty-nine (52.7%) of the private practitioners suspected TB in patients with three weeks' duration of cough. Only 37 (33.0%) of the private practitioners were able to precisely list the correct treatment regimens for all categories as recommended in the National Tuberculosis and Leprosy Control Program guidelines. The correct frequency of TB treatment monitoring was provided by 44 (50%) of the respondents.  Overall 44 (39.3%) of the private practitioners did not have satisfactory knowledge about the directly observed treatment short course (DOTS) strategy. Those who attended DOTS training during the two years prior to the survey were more likely to have satisfactory knowledge compared to those who did not receive training (OR 4.45, 95% CI: 1.33, 14.87, p < 0.02). Conclusion: A significant proportion of private practitioners did not have satisfactory knowledge and practice about DOTS. The provision of regular DOTS refresher courses improves TB management for patients in the region.